Frequent nucleation events at the high altitude station of Chacaltaya (5240 m a.s.l.), Bolivia. (February 2015) - Rose, C.; Sellegri, K.; Velarde, F.; Moreno, I.; Ramonet, M.; Weinhold, K.; Krejci, R.; Ginot, Patrick; Andrade, M.; Wiedensohler, A.; Laj, P.
Abstract: While nucleation may represent one of the major processes responsible for the total aerosol number burden in the atmosphere, and especially at high altitude, new particle formation (NPF) events occurring in the upper part of the troposphere are poorly documented in the literature, particularly in the southern hemisphere. NPF events were detected and analyzed at the highest measurement site in the world, Chacaltaya (5240 m a.s.l.), Bolivia between January 1 and December 31 2012, using a Neutral Aerosol and Ion Spectrometer (NAIS) that detects clusters down to 0.4 nm. NPF frequency at Chacaltaya is one of the highest reported so far (63.9%) and shows a clear seasonal dependency with maximum up to 100% during the dry season. This high seasonality of the NPF events frequency was found to be likely linked to the presence of clouds in the vicinity of the station during the wet season. Multiple NPF events are seen on almost 50% of event days and can reach up to 6 events per day, increasing the potential of nucleation to be the major contributor to the particle number concentrations in the upper troposphere. Ion-induced nucleation (IIN) was 14.8% on average, which is higher than the IIN fractions reported for boundary layer stations. The median formation rate of 2 nm particles computed for first position events is increased during the dry season (1.90 cm −3  s −1 ) compared to the wet season (1.02 cm − 3  s −1 ), showing that events are more intense, on top of being more frequent during the dry season. On the contrary, particle growth rates (GRs) are on average enhanced during the wet season, which could be explained by higher amount of biogenic volatile organic compounds transported from the Amazon rainforest. The NPF events frequency is clearly enhanced when air masses originate from the oceanic sector, with a frequency of occurrence close to 1. However, based on the particle GRs, we calculate that particles most likely nucleate after the oceanic air masses reach the land and are presumably not originating from the marine free troposphere. The high frequency of NPF events, the occurrence of multiple events per day, and the relatively high formation rates observed at Chacaltaya imply that nucleation and growth are likely to be the major mechanism feeding the upper atmosphere with aerosol particles in this part of the continent. Highlights: We detect and analyze new particle formation events at high altitude in Bolivia. Nucleation frequency is one of the highest reported in the literature. New particle formation is favoured during the dry season. Multiple daytime nucleation events are frequently observed. Particle growth is favoured in air masses that travelled over the Amazon rainforest.